GREEN CORROSION INHIBITOR ( THYME OIL) LOADED HNT FOR CORROSION PROTECTION OF CARBON STEEL - Mohd Khalid, Muhammad Azrai (IRC, 2020)
Carbon steel is mainly used in any industry applications and always been related to the main problem which is corrosion. New advanced technology is being applied to inhabit the corrosion problem by using the green corrosion inhibitor which using the inhibitor from the natural sources that free from the heavy metal, eco-friendly and mainly will not hazardous and yield any harm to the environment. Nowadays, many studies have been performed regarding to the green corrosion inhibitor where using the natural sources to organic compound such as aromatic herbs, species and medicinal plants.